(untitled) (Medical Forum Monthly, 2024)
Objective: To determine efficacy of glucosamine and chondroitin sulfate along with other conservative measures like education, analgesics, physiotherapy and intra-articular corticosteroids injections in management of osteoarthritis of knee joints Study Design: A prospective observational study Place and Duration of Study: This study was conducted at the Department of Orthopedic Surgery of different public and private hospitals of Karachi, during February 2017 to January 2018. Materials and Methods: There were 1732 patients in this study. The inclusion criteria were proper examination & radiological evidence for diagnosis of osteoarthritis of knee joints. Every patient was given Glucosamine 1500 mg per day and Chondroitin Sulfate 1200 mg per day. Analgesics were given as per requirement of the patient; physiotherapy was recommended to all the patients of knee joints osteoarthritis and intra-articular corticosteroid were given to patients with mild to moderate osteoarthritis of knee joints. Results: In our study out of 1732 patients 69% were female and 31% were male. Age ranges from 35 years to 60 and above years. All types of socio-economic classes were affected equally. Out of 1732 patients 69 % were female while 31% were male patients. 62% of the patients having involvement of osteoarthritis of both knee joints. We found 24% of patients have excellent improvement in quality of life, 37% of patients have good improvement in quality of life and 39% of patients have no significant improvement in quality of life. Conclusion: It is concluded that Glucosamine 1500 mg per day and Chondroitin Sulfate 1200 mg per day has shown effective results in management of osteoarthritis of knee joints of mild to moderate osteoarthritis.